2021
DOI: 10.1021/acsami.1c14519
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Strategies for High Photoluminescence Quantum Yield of Monolayer Chemical Vapor Deposition Transition Metal Dichalcogenides

Abstract: Chemical vapor deposition (CVD) is a promising method to obtain monolayer transition metal dichalcogenides (TMDCs) with high quality and enough size to meet the requirements of practical photoelectric devices. However, the as-grown monolayers often exhibit a lower PL performance due to the stress between the as-grown TMDCs flakes and the substrate. Therefore, finding a facile method to effectively promote the photoluminescence quantum yield (PL QY) of CVD monolayer TMDCs with a clean surface is highly desirabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In perspective, the here reported concept of 2D memitter can be introduced into a technological process flow by improving the lateral size of the deposited films (ideally to the wafer scale) and by boosting the quantum yield via interface engineering [52] or chemical methods, [53] thus aiming at expanding the matrix dimensions for VSTM applications by considering physical properties of other monolayer materials or intriguing combination of them in the heterostructure fashion, [54] where the spatial resolution of processable input patterns projected on the 2D material relies only on the laser spot size (Figure S5, Supporting Information). Furthermore, the rational design of 2D memitters can be developed by controlling and tuning the synaptic response by environmental conditions, laser excitation energy and power density.…”
Section: Discussionmentioning
confidence: 99%
“…In perspective, the here reported concept of 2D memitter can be introduced into a technological process flow by improving the lateral size of the deposited films (ideally to the wafer scale) and by boosting the quantum yield via interface engineering [52] or chemical methods, [53] thus aiming at expanding the matrix dimensions for VSTM applications by considering physical properties of other monolayer materials or intriguing combination of them in the heterostructure fashion, [54] where the spatial resolution of processable input patterns projected on the 2D material relies only on the laser spot size (Figure S5, Supporting Information). Furthermore, the rational design of 2D memitters can be developed by controlling and tuning the synaptic response by environmental conditions, laser excitation energy and power density.…”
Section: Discussionmentioning
confidence: 99%
“…As a reference sample, we utilized a thin poly(methyl methacrylate) (PMMA) film that contained dispersed rhodamine 6G (R6G). [43][44][45] We acquired photoluminescence (PL) spectra from a 300 nm-thick PMMA film with a concentration of 10 −4 M of R6G and from a bare quartz substrate. These spectra were measured utilizing an integrating sphere under a 514 nm laser excitation.…”
Section: Quantum Yield Measurementmentioning
confidence: 99%
“…Similarly, Chen et al demonstrated that the PLQYs of both MoS 2 and MoSe 2 were enhanced by the solvent with a moderate volatilization rate like ethanol. 132…”
Section: Mechanisms Of Chemical Passivationmentioning
confidence: 99%